IMAGE SYNTHESIS OF METAL FOAM MICRO-STRUCTURE WITH THE USE OF WANG TILES - Lukáš Zrůbek; Martin Doškář; Anna Kučerová; Marcela Meneses-Guzmán; Francisco Rodríguez-Méndez; Bruno Chiné (Acta Polytechnica CTU Proceedings, 2018)
In this paper we present our recent work focused on the analysis of the abilities of Wang Tiles method and Automatic tile design method to synthesize the micro-structure of cellular materials, especially particular type of metal foam. Wang Tiles method stores and compress the micro-structure in a set of Wang Tiles and by the means of stochastic tiling algorithms the planar domain is reconstructed. The used tiles are created by the Automatic tile design method from respective number of small specimens extracted from the original micro-structure image. As an additional step the central areas of automatically designed tiles are patched to suppress the influence of repeating tile edges (and relevant tile quarters) on inducing artifacts. In the presented analysis the performance of raw and patched tiles of different sizes in conjunction of various tile sets is investigated.